2015
DOI: 10.1007/s10208-015-9260-1
|View full text |Cite
|
Sign up to set email alerts
|

Plane Wave Discontinuous Galerkin Methods: Exponential Convergence of the $$hp$$ h p -Version

Abstract: We consider the two-dimensional Helmholtz equation with constant coefficients on a domain with piecewise analytic boundary, modelling the scattering of acoustic waves at a sound-soft obstacle. Our discretisation relies on the Trefftzdiscontinuous Galerkin approach with plane wave basis functions on meshes with very general element shapes, geometrically graded towards domain corners. We prove exponential convergence of the discrete solution in terms of number of unknowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…By combining an h-refinement near solution singularities with a p-refinement in the elements where the solution is sufficiently smooth, exponential convergence of the errors in terms of a proper root of the number of degrees of freedom is expected. In the framework of Trefftz methods for the Helmholtz equation, a full hp-analysis was investigated for the PWDG method [30], where exponential convergence in terms of the square root of the number of degrees of freedom was proven.…”
Section: Hp-versionmentioning
confidence: 99%
“…By combining an h-refinement near solution singularities with a p-refinement in the elements where the solution is sufficiently smooth, exponential convergence of the errors in terms of a proper root of the number of degrees of freedom is expected. In the framework of Trefftz methods for the Helmholtz equation, a full hp-analysis was investigated for the PWDG method [30], where exponential convergence in terms of the square root of the number of degrees of freedom was proven.…”
Section: Hp-versionmentioning
confidence: 99%
“…Although the so-called pollution effect is not avoidable for the classical Helmholtz equation in dimension d ≥ 2 as shown in [4], much work in its reduction has been invested: Examples of the proposed methods are the hp-version of the finite element method [23,41], (hybridizable) discontinuous Galerkin methods [15,29], or plane wave Trefftz methods [33,34,47], just to name a few. Recently, it has been shown that the resolution condition can be relaxed to the natural assumption "kh sufficiently small" by applying a Localized Orthogonal Decomposition (LOD) to the Hemholtz equation, see [13,26,48].…”
Section: Quasi-optimality Of the Hmmmentioning
confidence: 99%
“…By now, the challenges for wave propagation problems on the one side and for high-contrast coefficients on the other side mostly have been studied separately. To reduce the pollution effect for the Helmholtz equation with constant or low-contrast coefficients, a number of approaches has been designed and analyzed, such as (hybridizable) discontinuous Galerkin methods [12,27], the hp-version of the finite element method [21,40,41,42], (plane wave) Trefftz methods [24,33,48], or the Localized Orthogonal Decomposition [10,23,50]. High-contrast coefficients mainly have been studied for elliptic problems using multiscale finite element methods [13,18,45] and the Localized Orthogonal Decomposition [29,51], just to name a few.…”
Section: Introductionmentioning
confidence: 99%